计算(1)(a+√ab+b)(√a-√b)(a≥0,b≥0) (2)(√5+1)(√5-1)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/04 03:12:00
计算(1)(a+√ab+b)(√a-√b)(a≥0,b≥0)(2)(√5+1)(√5-1)计算(1)(a+√ab+b)(√a-√b)(a≥0,b≥0)(2)(√5+1)(√5-1)计算(1)(a+√a
计算(1)(a+√ab+b)(√a-√b)(a≥0,b≥0) (2)(√5+1)(√5-1)
计算(1)(a+√ab+b)(√a-√b)(a≥0,b≥0) (2)(√5+1)(√5-1)
计算(1)(a+√ab+b)(√a-√b)(a≥0,b≥0) (2)(√5+1)(√5-1)
(1)(a+√ab+b)(√a-√b)(a≥0,b≥0)
=(√a-√b)^3
(2)(√5+1)(√5-1)=4
计算√(1/b-1)·√(ab-a)
计算:√(ab)×2√(b/a)×(-√a/b)(-√1/ab)
计算[(√ab ) -ab/(a+√ab)]÷(√ab)-b/a-b
已知/a-4/+√(b-9)=0,计算(a²+ab)/(b²)·(a²-ab)/(a²-b²)
计算.二次根式(a-b)/(√a-√b)-(a+b-2√ab)/(√a-√b)
√b+√a³b-(√b³+√1/ab) 计算
1.如果a+b=-1,ab=-3计算 :(1)b/a + a/b
计算a²/(a²-2ab)×√(a²b-4ab²+4b^3)/a+b√(a/b) (0<a<2b)
计算(a/a-b+b/b-a)/(1/a+b)的结果 (1)a-b (2)ab (3)a^2-b^2 (4)a+b
计算:a/b(a-b)-b/a(a-b);(1/a+1/b)÷a²+2ab+b²/a+b.
计算 (a+b)(a*2-ab+b*2)
计算:(a-b)(a²+ab+b²)
计算((a+b)2-(a-b)2)/2ab
计算:(a+b)²-4ab
计算:1、√2×3√2 2、5√ab·(-4√a³b)(a≥0,b≥0) 3、√a³b的六次方+√ab(a>0,b>0)4、b分之2√ab的5次方·(-二分之三√a³b)÷3√a分之b
计算:1、√2×3√2 2、5√ab·(-4√a³b)(a≥0,b≥0) 3、√a³b的六次方+√ab(a>0,b>0)4、b分之2√ab的5次方·(-二分之三√a³b)÷3√a分之b
计算:[a²/(a-b)+b²/(b-a)]/[(a+b)/ab]
a√(a/b)÷√ab×√(1/ab)(b>0)